PROBLEMS OF INFLATION, UNEMPLOYMENT AND INCOME DISTRIBUTION IN THE TRANSITION OF EASTERN BLOC COUNTRIES TO MARKET ECONOMY: EXAMPLES FROM SELECTED REGIONAL COUNTRIES - Yrd. Doç. Dr. Remzi Bulut (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The Eastern bloc fell with the unification of Germany and the fall of Soviet Union, Czechoslovakia and Yugoslavia. After the year 1991, the countries that consisted the old Eastern Bloc went in a pursuit of a new economical and political system. Generally, all of the transiting countries have adopted a transition towards a market economy. Because of this reason, the ex Eastern Bloc countries are also known as "Transition Countries" or "Transition Economies". These countries have started the reforms of transition to a market economy after the first years of the disbanding of the Eastern Bloc. With the beginning of the reforms, macro economical problems rose due to the change of systems. The most important of these problems are; inflation, unemployment and injustices in income distribution. In this work, theoretical information is provided about transition economies, transition periods and transition reforms. Besides, the problems of income distribution, unemployment and inflation in the select transition countries are discussed. As a result of this study it was concluded that transition reforms have an impact on inflation and unemployment and unemployment and inflation have an impact on per capita income.